Diagnostic Yield of Micro-Computed Tomography (micro-CT) Versus Histopathology of a Canine Oral Fibrosarcoma. (March 2020) - Eberspächer-Schweda, Matthias C.; Schmitt, Kira; Handschuh, Stephan; Fuchs-Baumgartinger, Andrea; Reiter, Alexander M.
Micro-computed tomography (micro-CT) imaging currently gains increased interest in human as well as veterinary medicine. The ability to image 3-dimensional (3D) biopsy specimens nondestructively down to 1 µm spatial resolution makes it a promising tool for microscopic tissue evaluation in addition to histopathology. Visualizing tumor margins and calculating tumor load on 3D reconstructions may also enhance oncological therapies. The objective of this study was to describe the workflow from tumor resection to histopathological diagnosis, using both routine hematoxylin-eosin (HE)-stained sections and micro-CT tomograms on a stage II oral fibrosarcoma in a 7-year-old Hovawart dog. The maxillectomy specimen was fixed with formalin and stained with an X-ray dense soft tissue contrast agent. Micro-CT imaging was done using an ex vivo specimen micro-CT device. Tumor margins could not be exactly determined on micro-CT tomograms due to limited image resolution and contrast. Histopathology was performed after washing out the contrast agent. It showed neoplastic cells infiltrating the surrounding tissue further than assumed from micro-CT images. A total tumor volume of 10.3 cm 3 could be calculated based on correlating micro-CT tomograms with HE-stained sections. This correlative approach may be of particular interest for oncological therapy. More than that, micro-CT imaging technology supported histopathology by means of 3D orientation and selection of slices to be cut on determining tumor margins. In this clinical case report, micro-CT imaging did not provide unambiguous clinical evidence for oncological decision-making, but it showed potential to support histopathology and calculate tumor volume for further clinical use.